PEMANFAATAN MEDIA SOSIAL TIKTOK SEBAGAI SUMBER INFORMASI GEN Z DI KALANGAN MAHASISWA ILMU KOMUNIKASI - Putri Aprillia Syavira; RR Roosita Cindrakasih; Sultan Himawan (CV Edujavare Publishing, 2025)
This research is motivated by the phenomenon of the increasing use of TikTok as a source of information among Gen Z students, especially Communication Science students. In today's digital era, information consumption patterns have changed significantly; the younger generation tends to choose fast, concise, and interactive platforms such as TikTok. Through the Uses and Gratification theory, this study explains that students are not only passive recipients, but actively select, sort, and interpret content that suits their needs, both for entertainment and educational purposes. With a descriptive qualitative approach and in-depth interview and observation methods, researchers found that TikTok is used as an alternative media in finding light but meaningful information, especially related to social issues, academics, and public communication trends. Communication Science students show a selective attitude and are quite critical in assessing the accuracy and relevance of the content consumed. The results of this study indicate that TikTok is not only an entertainment media, but also a digital learning space that can encourage media literacy if utilized wisely. The contribution of this research is to provide a real picture of the dynamics of Gen Z information consumption, as well as a reference for educational institutions and policy makers to better understand the mindset of the younger generation in the era of fast-paced digital information.